PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM EFISIENSI ADMINISTRASI KEPENDIDIKAN - Adha Marche Lino Untajana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the utilization of Artificial Intelligence (AI) in improving the efficiency of educational administration, specifically addressing the acute administrative overload faced by teachers. Employing a library research approach with a narrative literature review design, this study analyzed 16 accredited SINTA journal articles published between 2022 and 2026. Data were collected from various databases and analyzed using a thematic-qualitative approach. The results indicate that AI contributes significantly to reducing teachers' administrative burden by 60–80%, accelerating assessment processes, enhancing data accuracy, and transforming educational leadership from conventional models to data-driven digital leadership. Furthermore, AI mitigates extraneous cognitive load, allowing teachers to focus on meaningful pedagogical activities. However, the implementation of AI faces structural challenges, including limited digital infrastructure, suboptimal teacher digital competence, data privacy risks, and potential algorithmic bias. The study concludes that the successful integration of AI in educational administration requires a holistic approach encompassing infrastructure development, human capacity building, ethical governance, and supportive policies. These findings imply the urgent need for national AI ethics guidelines, strengthened digital infrastructure, and continuous training programs for educators to ensure equitable and transparent educational management.